Changes in Interleukins and Follicle Stimulating Hormone in Toxoplasmosis Male Patients - Alia Salim Altemeemi1 , Noor Kareem Kadhim2 , Ghufran Saad Nsaif3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
In several countries there are endemic of parasitic diseases, specifically in developing countries, severalstudies investigated that toxoplasmosis is related with sterility of male. Aims of study are assessment of antiToxoplasma IgG antibodies in patient’s serum and their relation with interleukins and FSH hormone. IL-6stimulates antibody production and extend effect of proinflammatory by stimulating the production of acutephase proteins. IL-10 and IL-12 control the immune response type. Cytokine synthesis is inhibits by theformer and by blocking the IL-6 and TNF-? production, the response with involvement of Th2 and activationof B cells has an advantage. Detection for the toxoplasmosis which is based on toxo IgG , interleukins andFSH used the classic ELISA technique that based on immunoassay system using fluorescence technologyand antigen antibody interaction. They were found in 1 (3.03%) of azoospermic patients and 4(12.12%)of oligozoospermic patients, while the negative results found in 32(96.97%) of azoospermic patients and29(87.88%) of oligozoospermic patients. The control group had 34(100%) negative results in toxoplasmosis.The mean serum levels of IL-6 and IL-17 (pg / ml) increased significantly in patients with Toxoplasma gondiicompared to the control group (237.97±9.09 pg / ml 285.52±12.45and pg / ml, respectively; p<0.0001) . Inthis study, it has been concluded that infection with T. gondii can effect on the level of the interleukins andFSH in infertile couples.